Calcium signaling through CaMKII regulates hepatic glucose production in fasting and obesity - Ozcan, Lale; Backs, Johannes (Cell metabolism, 2012)
Summary Hepatic glucose production (HGP) is crucial for glucose homeostasis, but the underlying mechanisms have not been fully elucidated. Here, we show that a calcium-sensing enzyme, CaMKII, is activated in a calcium- and IP3R-dependent manner by cAMP and glucagon in primary hepatocytes and by glucagon and fasting in vivo. Genetic deficiency or inhibition of CaMKII blocks nuclear translocation of FoxO1 by affecting its phosphorylation, impairs fasting- and glucagon/cAMP-induced glycogenolysis and gluconeogenesis, and lowers blood glucose levels, while constitutively active CaMKII has the opposite effects. Importantly, the suppressive effect of CaMKII deficiency on glucose metabolism is abrogated by transduction with constitutively nuclear FoxO1, indicating that the effect of CaMKII deficiency requires nuclear exclusion of FoxO1. This same pathway is also involved in excessive HGP in the setting of obesity. These results reveal a calcium-mediated signaling pathway involved in FoxO1 nuclear localization and hepatic glucose homeostasis.
Gesehen am 02.05.2018